Upaya Konselor Hukum (UPTD PPA) Dalam Menangani Kasus Pelecehan Seksual Remaja Perempuan - Fachri Fadilah Taufik; Janessa Amara Maharani; Salma Sakinah; Syahlita Aulia Salma; Yani Achdiani; Gina Indah Permata Nastia; Sarah Nurul Fatimah (CV. ITTC INDONESIA, 2025)
This study aims to explore the role and efforts of legal counselors at the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA) in West Java Province in handling cases of sexual harassment against adolescent girls aged 12–18. A qualitative descriptive method was used, with data collected through in-depth interviews, field observations, and documentation. The main informant was Ma’ruf, a legal counselor directly involved in assisting victims. The findings reveal that legal counselors not only provide legal assistance but also emotional support throughout the legal process. Major challenges include low legal literacy among victims and their families, societal stigma, and a lack of professional support personnel. The study recommends age-appropriate sexual education, increased legal awareness, and cross-sectoral collaboration as strategic measures to protect adolescent girls from sexual violence.